Las situaciones comunicativas reales, basadas en la Conciencia Fonológica, mejoran la lectura y escritura en las niñas del primer grado de Educación Primaria de la Institución Educativa Nº 81007 “Modelo” – Trujillo, 2016 - Lozano Mejía, Edith Lizeth (2017)
The main objective of this research is to demonstrate that "Real communicative situations based on phonological awareness" improves the reading and writing learning of first grade students of Trujillo Educational Institution Nº 81007._x000D_ The sample population consisted of 28 girls from the experimental group and 28 girls from the control group. Whose ages range between 6 and 7 years, being the experimental group to whom the research project "Real communicative situations based on phonological awareness" was applied; Using as an application scenario the classroom of the Educational Institution. The type of research is applied with a Quasi Experimental design, having an Experimental Group and a Control Group._x000D_ The results obtained later indicated that the girls in the experimental group improved significantly in reading and writing. While in the control group, the students did not show a significant improvement.